Three rooms - Hamya, Jo, 1997- (Houghton Mifflin Harcourt, 2021)
"A piercing howl of a novel about one young woman's endless quest for an apartment of her own and the aspirations and challenges faced by the millennial generation as it finds its footing in the world, from a shockingly talented debut author"--